Norfloxacin penetration into subcutaneous tissue cage fluid in rabbits and efficacy in vivo. - Rylander, M (1983)
The activity of norfloxacin was studied in vivo with steel net cages implanted subcutaneously in rabbits. Four weeks after implantation, two of four cages in each animal were inoculated with a strain of Escherichia coli (seven animals) or Klebsiella pneumoniae (six animals). Four animals in each group received oral treatment with norfloxacin for 7 days. Treatment was started 18 h after inoculation of the cages. Peak concentrations above the in vitro minimal inhibitory concentrations for the strains used were achieved in the fluid of 14 of 16 of the infected cages after the first norfloxacin dose. The penetration of norfloxacin into both infected and uninfected tissue cage fluid was significantly higher on treatment days 3 and 7 than on treatment day 1. No difference was observed between the concentrations in uninfected and infected cage fluids or between cage fluids infected with different organisms. The viable counts of E. coli and K. pneumoniae decreased from 2 X 10(3) to 2 X 10(8) CFU/ml of cage fluid to less than 10 CFU/ml in 10 of the infected cage fluids 12 h after the last dose of norfloxacin. Fluid from four cages still containing low numbers of viable bacteria at that time became free from bacteria (less than 10 CFU/ml) 1 to 4 days later. No regrowth was found in any cage fluid 7 days after the treatment period. The viable counts of E. coli or K. pneumoniae in five untreated control animals did not decrease during 8 to 14 days after inoculation of cage fluid. In comparison with cephalosporins and aminoglycosides studied previously with the same experimental method, norfloxacin penetrated better into cage fluid and more effectively reduced the viable counts of the organisms.